Analysis of the Chemical Content of Coconut Husk as a Raw Material for Furfural Production - Dewi Arziyah; Anwar Kasim; Alfi Asben; Munzir Busniah (Green Engineering Society, 2025)
Coconut-based production generates waste such as coconut husk, which contains up to 35% lignocellulose—a valuable raw material for furfural production. This study aimed to determine the impact of coconut maturity level and coconut husk section on the lignocellulose content in coconut husk. This study used a randomized group design with two factors: coconut maturity level and coconut husk section. The variables observed were moisture, extractive, cellulose, hemicellulose, and lignin contents. Analysis of Variance (ANOVA) was performed for data analysis, followed by Duncan's Multiple Range Test (DMRT). The coconut fruits used were immature and mature ones. This study analyzed the husk at the proximal end, equator, and distal end of the coconut fruit. The results show significant effects of coconut maturity level on the chemical composition of coconut husk at the three sections of the coconut, indicating coconut husk’s potential as a raw material for furfural production.